The twinned crystal structure of 10-(4-methyl benzoate)-2,8-diethyl-5,5-difluoro-1,3,7,9-tetramethyl-5H-di-pyrrolo[1,2-c:2′,1′-f] [1,3,2]diazaborinin-4-ium-5-uide, C25H29BF2N2O2 - Usman Rabia; Bin-Jumah May Nasser; Altamimi Abeer A.; Baeshen Kholoud A.; Feng Chao; Al-Qhatani Mohsen Mohammed; Henidi Hanan A. (Zeitschrift für Kristallographie - New Crystal Structures)
C25H29BF2N2O2, triclinic, P1 $P1$ (no. 1), a = 7.5649(4) Å, b = 7.6172(5) Å, c = 10.4163(6) Å, α = 73.672(5)°, β = 78.776(5)°, γ = 82.641(5)°, V = 563.28(6) Å3, Z = 1, R gt(F) = 0.0390, wR ref(F 2) = 0.1081, T = 150 K.